Preparation of environment-friendly solid epoxy resin with high-toughness via one-step banburying. Issue 26 (6th June 2022) - Lou, Gaobo; Li, Qing; Jin, Qian; Rao, Qingqing; Fu, Shenyuan; Dai, Jinfeng
Abstract : High-toughness and environment-friendly solvent free solid epoxy resin through a low-cost, facile and large-scale fabrication process. Abstract : Solid epoxy resin is highly desired in adhesives, electronic materials and coatings due to the attractive characteristics of solvent-free, highly efficient utilization and convenient storage and transportation. However, the challenges remain in fabricating high-toughness solid epoxy resin through a facile and efficient way. Here, a high-performance environment-friendly solid epoxy resin was fabricated by employing maleic anhydride grafted ethylene-vinyl acetate copolymer (EVA- g -MAH) as the flexibilizer via one-step banburying method. The results showed that the modified epoxy resin maintained a high glass transition temperature ( T g ) and thermal stability, while its impact strength, tensile toughness and flexural toughness were significantly increased compared with the neat epoxy resin. The impact strength, tensile toughness and flexural toughness of R-EM10 are improved 138%, 195% and 149%, respectively. The EVA- g -MAH was introduced in the epoxy matrix as a separate phase to increase toughness via transfer stress and dissipated energy. The attractive properties of this facile fabrication process and the high-toughness, as well as the environment-friendly performance make this solid epoxy highly promising for large-scale industrial application.